Fasciotomy in compartment syndrome from snakebite - Yong Hun Kim; Jin-hee Choi; Jiye Kim; Yoon Kyu Chung (Archives of Plastic Surgery, 2019)
Background Local symptoms and signs of snake envenomation mimic the clinical features of compartment syndrome. It is important to measure the intracompartmental pressure to diagnose compartment syndrome. In this study, we present our experiences of confirming compartment syndrome and performing fasciotomy in snakebite patients based on high intracompartmental pressure findings. Methods The medical records of patients who visited the trauma center of Wonju Severance Christian Hospital from January 2010 to December 2015 for the management of venomous snakebite were retrospectively reviewed. Starting in 2014, fasciotomy was performed in patients with an intracompartmental pressure of more than 40 mmHg in addition to the clinical symptoms of compartment syndrome. Results A total of 158 patients with snakebite came to the hospital within 48 hours for treatment. Most patients (110 patients) were bitten at the upper extremities (69.6%). Since 2014, 33 out of 59 patients were suspected to have compartment syndrome, and their intracompartmental pressures were measured. Seventeen of those patients had a high intracompartmental pressure (average, 49.6 mmHg; range, 37–88 mmHg), and fasciotomy was performed. Conclusions In this study, as many as 10.8% of all cases were in need of fasciotomy when compartment syndrome was diagnosed by measuring the intracompartmental pressure. Previously, it was reported that fasciotomy was not required in many cases of compartment syndrome originating from snakebite. However, some patients may develop very severe compartment syndrome, requiring fasciotomy.